Pertanggungjawaban Pelanggaran Hak Cipta yang Dilakukan oleh Korporasi - Yohanes Reston N.A Laia; Yasmirah Mandasari Saragih; Sari Sania Tampubolon; Faisal Faisal; Andi Gultom (Pusat Riset dan Inovasi Nasional, 2025)
The acceleration of globalization and advances in information technology have brought about significant changes in the economic field. In this context, collaboration between individuals is a key element in forming business groups that aim to achieve economic benefits. These business groups can take the form of informal businesses that do not yet have legality, as well as legal entities known as corporations. When individuals join a corporation, this also strengthens the corporation's position as a legal subject in economic activities. A legal subject (subject tumjuris) is an entity that can have and exercise rights and obligations. This situation can trigger abuse of power by corporations against the public interest, which is then known as corporate crime. Such crimes are usually committed for the sake of the company's business interests and fall into the category of white collar. crime. One form of corporate crime that is rampant is the violation of the economic rights of creators and copyright owners